Silicon oxide aerogel composite material and preparation method thereof

By combining the silicon oxide aerogel with a frame matrix with pores and using supercritical drying and other processes, the problem of poor mechanical properties of silicon oxide aerogel materials is solved, and high thermal insulation performance and high mechanical properties are achieved.

CN119462066APending Publication Date: 2025-02-18DONGHUA UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411687383.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The mechanical properties of existing silicon oxide aerogel materials are poor, which limits their application, and the prior art is difficult to maintain high thermal insulation while improving mechanical properties.

Method used

By combining the silicon oxide aerogel with a frame matrix with pores (such as aramid honeycomb plates, wheat straw, hollow fibers), the silicon oxide aerogel is embedded in the pores of the frame matrix, and combined with supercritical drying and other processes, a silicon oxide aerogel has been prepared with a Silicon oxide aerogel composite material with excellent thermal insulation and mechanical properties.

Benefits of technology

It achieves the high thermal insulation performance and high mechanical properties of silicon oxide aerogel composite materials, improves the overall performance of the material, and is suitable for a variety of industrial and aerospace fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462066A_ABST
    Figure CN119462066A_ABST
Patent Text Reader

Abstract

The invention provides a silicon oxide aerogel composite material and a preparation method thereof. The silicon oxide aerogel composite material comprises a frame matrix with pores and silicon oxide aerogel, the silicon oxide aerogel is embedded in at least part of pores of the frame matrix; the frame base body comprises an aramid honeycomb plate, wheat straw and hollow fibers; the thickness of the aramid fiber honeycomb plate is 1-6 mm; the diameter of the wheat straw is 3-6 mm; the inner diameter of the hollow fiber is 300-500 [mu] m, and the outer diameter of the hollow fiber is 500-700 [mu] m. The silicon oxide aerogel composite material is prepared by embedding the silicon oxide aerogel as a filling body into the pores of the frame matrix, and the silicon oxide aerogel composite material has the advantages of high heat insulation performance and high mechanical performance, and meets the performance requirements on heat insulation materials in practical application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aerogel preparation, and in particular to a silicon oxide aerogel composite material and a preparation method thereof. Background Art

[0002] Thermal insulation materials can play an effective role in protection and energy conservation and emission reduction, so they have important application value in many fields such as modern industry, aerospace, civil, and industry. Among them, highly porous silica aerogel materials have become the most promising "super thermal insulation materials" due to their high thermal insulation performance, high porosity, and light weight. Although silica aerogel materials have high thermal insulation performance, since silica aerogel materials are three-dimensional skeleton structures formed by the accumulation of ultrafine nanoparticles, the connection between particles is weak, resulting in poor mechanical properties, which limits its application.

[0003] In order to improve the mechanical properties of silica aerogel, the prior art generally prepares silica aerogel based on an organic / inorganic hybrid strategy: (1) introducing an organic resin into silica at a molecular scale to prepare a silica aerogel material; (2) introducing an organic cellulose nanofiber skeleton into silica to prepare a silica aerogel material. For example, the patent technology with publication number CN105838022A discloses an organic / inorganic phenolic resin hybrid aerogel and a preparation method thereof, wherein phenolic resin and silica are used as raw materials, and an organic / inorganic hybrid phenolic resin aerogel is prepared by a mild reaction pathway and a normal pressure drying method. The compressive strength of the organic / inorganic hybrid phenolic resin aerogel is 0.675-0.887MPa. However, the preparation of the organic / inorganic hybrid phenolic resin aerogel not only requires complex molecular design, interface regulation and structural assembly, but also increases the difficulty of the preparation process, and the scalability of the process is challenged, and it still has the problem of poor mechanical properties (compressive strength is less than 1Mpa).

[0004] Therefore, how to obtain a silica aerogel composite material with both high thermal insulation performance and high mechanical properties is a technical problem that needs to be solved urgently in this field. Summary of the invention

[0005] The invention provides a silicon oxide aerogel composite material, which has excellent thermal insulation and mechanical properties.

[0006] The invention provides a method for preparing a silicon oxide aerogel composite material. The method has a simple process and can prepare a silicon oxide aerogel composite material with excellent thermal insulation and mechanical properties.

[0007] The invention provides a thermal insulation material, comprising the silicon oxide aerogel composite material, so the thermal insulation material has excellent thermal insulation performance and mechanical properties.

[0008] A first aspect of the present invention provides a silica aerogel composite material, comprising a framework matrix having pores and a silica aerogel;

[0009] The silica aerogel is embedded in at least part of the pores of the framework matrix;

[0010] The frame matrix includes aramid honeycomb panels, wheat straw, and hollow fibers;

[0011] The thickness of the aramid honeycomb panel is 1 mm to 6 mm;

[0012] The diameter of the wheat straw is 3 mm to 6 mm;

[0013] The inner diameter of the hollow fiber is 300 μm to 500 μm, and the outer diameter is 500 μm to 700 μm.

[0014] As mentioned above, in the silica aerogel composite material, the content of the silica aerogel is 34wt% to 70wt%, and the content of the framework matrix is ​​30wt% to 66wt%.

[0015] A second aspect of the present invention provides a method for preparing a silicon oxide aerogel composite material, comprising:

[0016] Compounding the silicon oxide aerogel with the framework matrix to obtain a silicon oxide wet gel composite material;

[0017] After aging the silicon oxide wet gel composite material, immersing it in a first solvent for primary replacement, and immersing it in a second solvent for secondary replacement to obtain a silicon oxide aerogel composite material precursor;

[0018] The silicon oxide aerogel composite material precursor is dried to obtain a silicon oxide aerogel composite material.

[0019] In the method for preparing the silica aerogel composite material as described above, the drying is supercritical drying, the temperature of the supercritical drying is 30° C. to 40° C., the time is 40 min to 60 min, and the pressure is 8 MPa to 12 MPa.

[0020] In the method for preparing the silica aerogel composite material as described above, the first solvent is at least one of water, ethanol, and isopropanol, and the second solvent is at least one of ethanol and isopropanol.

[0021] The method for preparing the silica aerogel composite material as described above, wherein the aging treatment temperature is 60° C. to 80° C. and the time is 10 h to 12 h;

[0022] And / or, the one replacement is multiple replacements, the number of the multiple replacements is 2 to 5 times, and the time of each replacement in the multiple replacements is 6 hours to 12 hours;

[0023] And / or, the secondary replacement is several replacements, the number of the several replacements is 4 to 6 times, and the time for each replacement in the several replacements is 6 hours to 12 hours.

[0024] The method for preparing the silica aerogel composite material as described above, wherein the silica aerogel is prepared by the following steps:

[0025] The organic siloxane, acetic acid aqueous solution, urea and surfactant are mixed and subjected to hydrolysis and condensation reaction to obtain silica sol;

[0026] The silica sol is subjected to the action of a pH regulator to obtain the silica gel.

[0027] In the method for preparing the silica aerogel composite material as described above, the mass ratio of the organosiloxane, the acetic acid aqueous solution, the urea and the surfactant is (3-8): (12-18): (3-8): (0.5-1.5).

[0028] The method for preparing the silica aerogel composite material as described above, wherein the organosiloxane is at least one of methyltrimethoxysilane, ethyltrimethoxysilane, vinyltrimethoxysilane, and propyltrimethoxysilane;

[0029] And / or, the surfactant is at least one of cetyltrimethylammonium chloride, cetyltrimethylammonium bromide, and polyoxyethylene polyoxypropylene ether.

[0030] And / or, the condensation reaction temperature is 60°C to 80°C and the time is 3h to 4h;

[0031] And / or, the pH adjuster includes acetic acid solution, and the pH value after adjustment by the pH adjuster is 3-4.

[0032] A third aspect of the present invention provides a thermal insulation material comprising the above-mentioned silica aerogel composite material.

[0033] The silica aerogel composite material provided by the present invention comprises silica aerogel and a frame matrix, wherein the silica aerogel is embedded in at least part of the pores of the frame matrix, and the silica aerogel and the frame matrix work together to effectively block heat and improve the mechanical properties of the silica aerogel composite material. Compared with the existing fiber-reinforced silica aerogel, the silica aerogel composite material provided by the present invention has better mechanical properties and processability.

[0034] The present invention provides a method for preparing a silica aerogel composite material. The preparation method is simple and does not require the destruction of raw materials. The existing frame matrix (aramid honeycomb panel, wheat straw or hollow fiber) is directly composited with the silica aerogel, thereby maintaining the high thermal insulation performance of the silica aerogel and the high mechanical properties of the frame matrix. Therefore, the preparation method can prepare the above-mentioned silica aerogel composite material with excellent thermal insulation performance and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is an appearance diagram of the silicon oxide aerogel composite material of Example 1 of the present invention;

[0036] Figure 2 This is an appearance diagram of the silicon oxide aerogel composite material of Example 3 of the present invention;

[0037] Figure 3 This is an appearance diagram of the silicon oxide aerogel composite material of Example 4 of the present invention;

[0038] Figure 4 This is a test of the thermal insulation performance of the silica aerogel composite material of Example 1 of the present invention;

[0039] in, Figure 4 A is the thermal insulation performance test at a hot stage temperature of 100°C, where a is a silica aerogel composite material and b is an aramid honeycomb panel;

[0040] B is a thermal insulation performance test at a cold table temperature of -20°C, where a is a silica aerogel composite material and b is an aramid honeycomb panel. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Unless otherwise specified, the raw materials and reagents used in the following examples can be obtained from commercial sources; the processes used, unless otherwise specified, are conventional processes in the art.

[0043] It should be noted that, in the present invention, there are descriptions involving "once", "secondly", "first", "second", etc., and the descriptions of "once", "secondly", "first", "second", etc. are only used for descriptive purposes and therefore cannot be understood as limitations on the present invention.

[0044] A first aspect of the present invention provides a silica aerogel composite material, comprising a framework matrix having pores and a silica aerogel;

[0045] Silica aerogel is embedded in at least a portion of the pores of the framework matrix;

[0046] The frame matrix includes aramid honeycomb panels, wheat straw, and hollow fibers;

[0047] The thickness of aramid honeycomb panels is 1mm to 6mm;

[0048] The diameter of wheat straw is 3mm to 6mm;

[0049] The inner diameter of the hollow fiber is 300 μm to 500 μm, and the outer diameter is 500 μm to 700 μm.

[0050] In the present invention, the silica aerogel is embedded in at least part of the pores of the framework matrix, which means that the silica aerogel can be embedded in part of the pores of the framework matrix, or can be embedded in the entire pores of the framework matrix.

[0051] The silica aerogel composite material of the present invention can use an aramid honeycomb panel with a thickness of 1 mm to 6 mm as a frame matrix, and the silica aerogel is embedded in at least part of the pores of the aramid honeycomb panel, and the silica aerogel composite material has excellent thermal insulation performance and mechanical properties; it can also use wheat straw with a diameter of 3 mm to 6 mm as a frame matrix, and the silica aerogel is embedded in at least part of the pores of the wheat straw, and the silica aerogel composite material has excellent thermal insulation performance and mechanical properties; it can also use a hollow fiber with an inner diameter of 300 μm to 500 μm and an outer diameter of 500 μm to 700 μm as a frame matrix, and the silica aerogel is embedded in at least part of the pores of the hollow fiber, and the silica aerogel composite material has excellent thermal insulation performance and mechanical properties.

[0052] The present invention has no particular limitation on the morphology of the silica aerogel composite material, and any conventional morphology familiar to those skilled in the art may be used, and those skilled in the art may select and adjust the morphology according to actual application conditions, product quality and product performance.

[0053] The present invention has no particular restriction on the source of the aramid honeycomb panel, wheat straw or hollow fiber, and they can be obtained from commercial sources.

[0054] The silicon oxide aerogel in the present invention can be prepared by the following steps:

[0055] The organic siloxane, acetic acid aqueous solution, urea and surfactant are mixed and subjected to hydrolysis and condensation reaction to obtain silica sol;

[0056] The silica sol is subjected to the action of a pH regulator to obtain a silica aerogel;

[0057] The organosiloxane is at least one of methyltrimethoxysilane, ethyltrimethoxysilane, vinyltrimethoxysilane and propyltrimethoxysilane; the surfactant is at least one of hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide and polyoxyethylene polyoxypropylene ether.

[0058] The present invention has no particular limitation on the selection of pH adjusters, and conventional pH adjusters known to those skilled in the art may be used. Those skilled in the art may select and adjust the pH adjuster according to actual production conditions, product quality, and product performance. The pH adjuster of the present invention preferably includes an acetic acid aqueous solution, and the pH value after adjustment by the pH adjuster is 3 to 4.

[0059] In some embodiments, the hollow fiber is one of hollow polypropylene fiber, hollow polyester fiber, and hollow nylon fiber. Further, the hollow fiber may preferably be hollow polypropylene fiber.

[0060] The present invention uses silica aerogel as a filler and embeds it into the pores of a frame matrix to prepare a silica aerogel composite material. The silica aerogel composite material has the advantages of high thermal insulation performance and high mechanical properties, and meets the performance requirements of thermal insulation materials in practical applications.

[0061] In a specific embodiment, in the silica aerogel composite material, the content of silica aerogel is 34wt% to 70wt%, and the content of the framework matrix is ​​30wt% to 66wt%.

[0062] When the content of the silica aerogel and the content of the framework matrix are respectively within the above ranges, a silica aerogel composite material having excellent thermal insulation and mechanical properties can be obtained.

[0063] A second aspect of the present invention provides a method for preparing a silicon oxide aerogel composite material, comprising:

[0064] Compounding the silicon oxide aerogel with the framework matrix to obtain a silicon oxide wet gel composite material;

[0065] After aging the silicon oxide wet gel composite material, the silicon oxide wet gel composite material is immersed in a first solvent for primary replacement, and immersed in a second solvent for secondary replacement to obtain a silicon oxide aerogel composite material precursor;

[0066] The silicon oxide aerogel composite material precursor is dried to obtain the silicon oxide aerogel composite material.

[0067] The selection, proportion and parameters of the raw materials in the above preparation method of the present invention, unless otherwise specified, correspond to the selection, proportion and parameters of the raw materials in the above-mentioned silicon oxide aerogel composite material, and will not be described in detail here.

[0068] The present invention does not specifically limit the specific method of composite treatment of silica aerogel and framework matrix, which can be selected according to actual needs. In some embodiments, the silica aerogel can be squeezed into the pores of the framework matrix by applying a pressure of 3kPa to 100kPa to obtain a silica wet gel composite material.

[0069] The present invention can prepare a silicon oxide aerogel composite material with excellent thermal insulation and mechanical properties through the preparation method.

[0070] In a specific embodiment, the drying is supercritical drying, and the supercritical drying temperature is 30° C. to 40° C., the time is 40 min to 60 min, and the pressure is 8 MPa to 12 MPa.

[0071] When the parameters of supercritical drying temperature, time and pressure are within the above ranges, the process of supercritical drying the silica aerogel composite precursor will not have a negative impact on the mechanical properties of the framework matrix, so the prepared silica aerogel composite not only maintains the high thermal insulation properties of the silica aerogel, but also maintains the high mechanical properties of the framework matrix.

[0072] Exemplarily, the temperature of supercritical drying may be any one of 30°C, 35°C and 40°C, and a range consisting of any two thereof;

[0073] The time may be any one of 40 min, 45 min, 50 min, 55 min and 60 min, or a range consisting of any two of them;

[0074] The pressure may be any one of 8 MPa, 9 MPa, 10 MPa, 11 MPa and 12 MPa, or a range consisting of any two of them.

[0075] In a specific embodiment, the first solvent is at least one of water, ethanol, and isopropanol, and the second solvent is at least one of ethanol and isopropanol.

[0076] The present invention immerses the aged silicon oxide wet gel composite material in the first solvent for a primary replacement, which can effectively remove the remaining urea and surfactant in the aged silicon oxide wet gel composite material; and immerses it in the second solvent for a secondary replacement, which can effectively remove the water in the silicon oxide wet gel composite material after the primary replacement, thereby avoiding the influence of impurities on the structure and performance of the silicon oxide aerogel composite material, and is conducive to preparing a silicon oxide aerogel composite material with excellent thermal insulation and mechanical properties.

[0077] In a specific embodiment, the aging temperature is 60° C. to 80° C., and the aging time is 10 h to 12 h.

[0078] When the parameters of aging temperature and time are within the above range, the unreacted raw materials in the silicon oxide wet gel composite material can be further reacted to make its gel network more compact, which is beneficial to the subsequent preparation of a silicon oxide aerogel composite material with excellent thermal insulation and mechanical properties.

[0079] Exemplarily, the aging temperature may be any one of 60°C, 65°C, 70°C, 75°C and 80°C, and a range consisting of any two thereof;

[0080] The time may be any one of 10 h, 10.5 h, 11 h, 11.5 h and 12 h, or a range consisting of any two of them.

[0081] In a specific embodiment, one replacement is multiple replacements, the number of multiple replacements is 2 to 5 times, and the time for each replacement in the multiple replacements is 6 hours to 12 hours.

[0082] When the parameters of the number of multiple replacements and the time of each replacement in the multiple replacements are within the above range, the remaining urea and surfactant in the silicon oxide wet gel composite material after aging treatment can be more effectively removed, which is conducive to obtaining a pure silicon oxide aerogel composite material and avoiding the influence of impurities on the structure and properties of the silicon oxide aerogel composite material.

[0083] Exemplarily, the number of multiple substitutions can be any one of 2, 3, 4 and 5 times, and a range consisting of any two of them;

[0084] The time of each replacement in the multiple replacements can be any one of 6 h, 7 h, 8 h, 9 h, 10 h, 11 h and 12 h, or a range consisting of any two of them.

[0085] In a specific embodiment, the secondary replacement is several replacements, the number of the several replacements is 4 to 6 times, and the time for each replacement in the several replacements is 6 hours to 12 hours.

[0086] When the parameters of the number of replacements and the time of each replacement in the replacements are within the above range, the water in the silicon oxide wet gel composite material after the above replacement can be more effectively removed. During the supercritical drying process, it is beneficial for the liquid CO2 to mix evenly with the second solvent in the silicon oxide aerogel composite material precursor, so that the structure of the prepared silicon oxide aerogel composite material is complete.

[0087] Exemplarily, the number of multiple substitutions can be any one of 2, 3, 4 and 5 times, and a range consisting of any two of them;

[0088] The time of each replacement in the multiple replacements can be any one of 6 h, 7 h, 8 h, 9 h, 10 h, 11 h and 12 h, or a range consisting of any two of them.

[0089] In a specific embodiment, the silicon oxide aerogel is prepared by the following steps:

[0090] The organic siloxane, acetic acid aqueous solution, urea and surfactant are mixed and subjected to hydrolysis and condensation reaction to obtain silica sol;

[0091] The silica sol is treated with a pH regulator to obtain a silica aerogel.

[0092] The present invention adopts the above steps to prepare the silicon oxide aerogel, and then utilizes the silicon oxide aerogel to prepare a silicon oxide aerogel composite material with high thermal insulation performance and high mechanical performance.

[0093] In a specific embodiment, the mass ratio of the organosiloxane, the acetic acid aqueous solution, the urea and the surfactant is (3-8): (12-18): (3-8): (0.5-1.5).

[0094] When the mass ratio of the organosiloxane, the acetic acid aqueous solution, the urea and the surfactant is within the above range, a silica aerogel with high thermal insulation performance can be prepared, which is beneficial for preparing a silica aerogel composite material with excellent thermal insulation and mechanical properties using the silica aerogel.

[0095] Illustratively, the mass ratio of the organosiloxane, the acetic acid aqueous solution, the urea and the surfactant may be any one of 3:12:3:0.5, 5:15:5:0.8, 3:18:8:1.5, 8:12:3:0.5 and 8:18:8:1.5, and a range consisting of any four thereof.

[0096] In some embodiments, the concentration of the acetic acid aqueous solution is 8 mM to 12 mM. Further, the concentration of the acetic acid aqueous solution may preferably be 10 mM.

[0097] In a specific embodiment, the organosiloxane is at least one of methyltrimethoxysilane, ethyltrimethoxysilane, vinyltrimethoxysilane and propyltrimethoxysilane. When the above organosiloxane is selected, a hydrolysis condensation reaction can be carried out by an acid-base two-step method to form a gel network.

[0098] In a specific embodiment, the surfactant is at least one of hexadecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, and polyoxyethylene polyoxypropylene ether. When the above surfactant is selected, the phase separation in the hydrolysis condensation reaction process can be effectively suppressed, thereby obtaining a silica aerogel with a uniform gel network structure.

[0099] In a specific embodiment, the condensation reaction temperature is 60° C. to 80° C., and the reaction time is 3 h to 4 h.

[0100] When the temperature and time parameters of the hydrolysis condensation reaction are within the above ranges, the organic siloxane, acetic acid aqueous solution, urea and surfactant can be fully hydrolyzed and condensed after mixing, which is beneficial to the subsequent preparation of a silica aerogel composite material with excellent thermal insulation and mechanical properties.

[0101] Exemplarily, the temperature of the condensation reaction may be any one of 60°C, 65°C, 70°C, 75°C and 80°C, and a range consisting of any two thereof;

[0102] The time can be any one of 3h, 3.5h and 4h, or a range consisting of any two of them.

[0103] In a specific embodiment, the pH adjuster includes an acetic acid solution, and the pH value after adjustment by the pH adjuster is 3-4.

[0104] When the pH value after adjustment by the pH adjuster is within the above range, a silica aerogel having fluidity can be obtained.

[0105] The third aspect of the present invention provides a thermal insulation material, comprising the above-mentioned silica aerogel composite material, so that the thermal insulation material has excellent thermal insulation performance and mechanical properties.

[0106] The present invention is further described below through specific embodiments.

[0107] Example 1

[0108] The preparation method of the silicon oxide aerogel composite material of this embodiment includes:

[0109] (1) 5 parts by weight of methyltrimethoxysilane, 15 parts of 10 mM acetic acid aqueous solution, 5 parts of urea and 0.8 parts of hexadecyltrimethylammonium chloride were mixed and stirred at room temperature for 30 minutes to obtain a clear silica sol.

[0110] (2) The clarified silica sol is transferred to a sealed glass bottle, and then the glass bottle is placed in an oven at 60°C. The clarified silica sol undergoes a hydrolysis and condensation reaction, and a gel network is gradually formed during the reaction. When the gel is about to lose its fluidity, the glass bottle is taken out of the oven and the pH (pH = 7) is tested. An acetic acid aqueous solution is added and stirred evenly to reduce the pH to 4, thereby obtaining a fluid silica aerogel.

[0111] (3) The silica aerogel was squeezed onto an aramid honeycomb panel (AT-NH-1.83-48, aramid honeycomb panel with a side length of 1.83 mm and a density of 48 kg / cm) with a thickness of 5 mm by applying a pressure of 5 kPa. 3, purchased from Suzhou Hangyu Composite Materials Co., Ltd.), and a silicon oxide wet gel composite material was obtained.

[0112] (4) The silicon oxide wet gel composite material was placed in an oven at 60° C. for aging treatment for 12 h and then immersed in water for replacement three times, with each replacement time being 8 h. The remaining urea and hexadecyltrimethylammonium chloride were removed to obtain the replaced silicon oxide wet gel composite material.

[0113] (5) The replaced silicon oxide wet gel composite material is placed in ethanol for secondary replacement 5 times, and the time for each replacement in the secondary replacement is 8 hours, and the water in the replaced silicon oxide wet gel composite material is removed to obtain a silicon oxide aerogel composite material precursor.

[0114] (6) The silica aerogel composite material precursor was subjected to supercritical drying at a temperature of 40° C. and a pressure of 9 MPa for 40 min to obtain Figure 1 The silica aerogel composite material shown (the content of silica aerogel is 59%, and the content of aramid honeycomb panel is 41%).

[0115] Example 2

[0116] The preparation method of the silicon oxide aerogel composite material of this embodiment is basically the same as that of embodiment 1, except that:

[0117] (3) The thickness of the aramid honeycomb panel is 2 mm.

[0118] Example 3

[0119] The preparation method of the silicon oxide aerogel composite material of this embodiment includes:

[0120] (1) By weight, 5 parts of propyltrimethoxysilane, 15 parts of 10 mM acetic acid aqueous solution, 5 parts of urea and 0.8 parts of polyoxyethylene polyoxypropylene ether were mixed and stirred at room temperature for 30 minutes to obtain a clear silica sol.

[0121] (2) The clarified silica sol is transferred to a sealed glass bottle, and then the glass bottle is placed in an oven at 60°C. The clarified silica sol undergoes a hydrolysis and condensation reaction, and a gel network is gradually formed during the reaction. When the gel is about to lose its fluidity, the glass bottle is taken out of the oven and the pH (pH = 7) is tested. An acetic acid aqueous solution is added and stirred evenly to reduce the pH to 4, thereby obtaining a fluid silica aerogel.

[0122] (3) The silica aerogel was squeezed into the pores of a wheat straw with a diameter of 3 mm (purchased from Taobao merchant Jingpin Department Store Zhou) by applying a pressure of 3 kPa to obtain a silica wet gel composite material.

[0123] (4) A silicon oxide wet gel composite material was placed in an oven at 60° C. for aging treatment for 12 h and then immersed in water for replacement three times, with each replacement time being 8 h. The remaining urea and hexadecyltrimethylammonium chloride were removed to obtain the replaced silicon oxide wet gel composite material.

[0124] (5) The replaced silicon oxide wet gel composite material is placed in ethanol for secondary replacement 5 times, and the time for each replacement in the secondary replacement is 8 hours, and the water in the replaced silicon oxide wet gel composite material is removed to obtain a silicon oxide aerogel composite material precursor.

[0125] (6) The silica aerogel composite material precursor was supercritically dried at a temperature of 40° C. and a pressure of 9 MPa for 40 min to obtain a silica aerogel composite material (the content of silica aerogel was 60% and the content of wheat straw was 40%).

[0126] (7) 13 silica aerogel composites were integrated by bonding technology to obtain Figure 2 The wheat straw silica aerogel sheet shown.

[0127] Example 4

[0128] The preparation method of the silicon oxide aerogel composite material of this embodiment is basically the same as that of embodiment 1, except that:

[0129] (1) 5 parts by weight of ethyltrimethoxysilane, 15 parts of 10 mM acetic acid aqueous solution, 5 parts of urea and 0.8 parts of hexadecyltrimethylammonium chloride were mixed and stirred at room temperature for 30 minutes to obtain a clear silica sol.

[0130] (2) The clarified silica sol is transferred to a sealed glass bottle, and then the glass bottle is placed in an oven at 60°C. The clarified silica sol undergoes a hydrolysis and condensation reaction, and a gel network is gradually formed during the reaction. When the gel is about to lose its fluidity, the glass bottle is taken out of the oven and the pH (pH = 7) is tested. An acetic acid aqueous solution is added and stirred evenly to reduce the pH to 4, thereby obtaining a fluid silica aerogel.

[0131] (3) The silica aerogel was squeezed into the pores of a hollow polypropylene fiber (purchased from Taobao merchant Haike Filter Membrane) with an inner diameter of 300 μm and an outer diameter of 500 μm by applying a pressure of 50 kPa to obtain a silica wet gel composite material.

[0132] (4) A silicon oxide wet gel composite material was placed in an oven at 60° C. for aging treatment for 12 h and then immersed in water for replacement three times, with each replacement time being 8 h. The remaining urea and hexadecyltrimethylammonium chloride were removed to obtain the replaced silicon oxide wet gel composite material.

[0133] (5) The replaced silicon oxide wet gel composite material is placed in ethanol for secondary replacement 5 times, and the time for each replacement in the secondary replacement is 8 hours, and the water in the replaced silicon oxide wet gel composite material is removed to obtain a silicon oxide aerogel composite material precursor.

[0134] (6) The silica aerogel composite material precursor was supercritically dried at a temperature of 40° C. and a pressure of 9 MPa for 40 min to obtain a silica aerogel composite material (the content of silica aerogel was 34% and the content of hollow polypropylene fiber was 66%).

[0135] (7) 100 silicon oxide aerogel composite materials were woven in warp and weft according to conventional methods to obtain Figure 3 Aerogel fiber braid shown.

[0136] Comparative Example 1

[0137] The preparation method of the silica aerogel composite material of this comparative example is basically the same as that of Example 1, except that:

[0138] (3) The thickness of the aramid honeycomb panel is 10 mm.

[0139] Comparative Example 2

[0140] The preparation method of the silica aerogel composite material of this comparative example is basically the same as that of Example 1, except that:

[0141] (6) In the silica aerogel composite material, the content of silica aerogel is 30%, and the content of aramid honeycomb panel is 70%.

[0142] Comparative Example 3

[0143] The preparation method of the silica aerogel composite material of this comparative example is basically the same as that of Example 3, except that:

[0144] (3) The diameter of wheat straw is 1 mm.

[0145] Comparative Example 4

[0146] The preparation method of the silica aerogel composite material of this comparative example is basically the same as that of Example 4, except that:

[0147] (3) The inner diameter of the hollow polypropylene fiber is 200 μm and the outer diameter is 300 μm.

[0148] Performance Characterization

[0149] 1. Appearance:

[0150] Figure 1 This is an appearance diagram of the silicon oxide aerogel composite material of Example 1 of the present invention; Figure 2 This is an appearance diagram of the wheat straw silica aerogel plate of Example 3 of the present invention; Figure 3 This is an appearance diagram of the aerogel fiber braid of Example 4 of the present invention;

[0151] like Figure 1 As shown, the outer frame of the silica aerogel composite material of Example 1 is composed of an aramid honeycomb panel, and the interior is uniformly filled with aerogel material.

[0152] like Figure 2 As shown, the outer frame of the wheat straw silica aerogel board of Example 3 is composed of wheat straw, and the interior is evenly filled with aerogel material. A triangular wheat straw silica aerogel board can be formed by bonding 13 silica aerogel composite materials.

[0153] like Figure 3 As shown, the outer frame of the aerogel fiber braid in Example 4 is composed of hollow polypropylene fibers, and the interior is evenly filled with aerogel materials. The aerogel fiber braid is obtained by weaving 100 silicon oxide aerogel composite materials in warp and weft.

[0154] 2. The following performance tests were performed on the silica aerogel composite materials of Examples 1-2, one silica aerogel composite material of Example 3, one silica aerogel composite material of Example 4, and the silica aerogel composite materials of Comparative Examples 1-4, respectively. The test results are shown in Table 1;

[0155] (1) Thermal conductivity (mW / m·K): in accordance with GB / T 10295-2008;

[0156] (2) Compression strength (MPa): in accordance with GB / T 1033.1-2008;

[0157] (3) Tensile strength (MPa): The mechanical properties of aerogel composites were tested using an INSTRON 5969 electronic universal testing machine at a tensile rate of 100 mm / min.

[0158] (4) Density (g / cm 3 ): According to GB / T 13350-2017.

[0159] Table 1 Test results

[0160]

[0161]

[0162] Analyze the data in the above table:

[0163] From Examples 1-4, it can be seen that silica aerogel can be composited with a variety of frame matrices (aramid honeycomb panels, wheat straw, hollow polypropylene fibers) to form a silica aerogel composite material having both high mechanical strength and high thermal insulation performance.

[0164] From the comparison between Example 1-2 and Comparative Example 1, it can be seen that by changing the thickness of the aramid honeycomb panel, it is found that the thermal conductivity is greatly affected by the thickness of the aramid honeycomb panel. As the thickness increases, it is speculated that the final thermal conductivity increases due to the improvement of solid heat conduction.

[0165] From the comparison between Example 1 and Comparative Example 2, it can be seen that by changing the content of silica aerogel and aramid honeycomb panel, it is found that the thermal conductivity will be affected by the different contents of silica aerogel and aramid honeycomb panel. As the content of silica aerogel increases, the thermal conductivity of the silica aerogel composite material decreases and the thermal insulation performance improves.

[0166] From the comparison between Example 3 and Comparative Example 3, it can be seen that by changing the diameter of the wheat straw, it is found that the thermal conductivity will be affected by the different diameters of the wheat straw. As the diameter of the wheat straw increases, the thermal conductivity of the silica aerogel composite material decreases and the thermal insulation performance improves.

[0167] From the comparison between Example 4 and Comparative Example 4, it can be seen that by changing the inner diameter and outer diameter of the hollow polypropylene fiber, it is found that the thermal conductivity will be affected by the different inner diameter and outer diameter of the hollow polypropylene fiber. As the inner diameter and outer diameter of the hollow polypropylene fiber increase, the thermal conductivity of the silica aerogel composite material decreases and the thermal insulation performance improves.

[0168] 3. Thermal insulation performance:

[0169] Thermal insulation performance test method: Use infrared thermal imaging to capture the surface temperature of the sample under 100°C (high temperature) and -20°C (low temperature) conditions.

[0170] The silica aerogel composite material and the aramid honeycomb panel in Example 1 were used as test samples to conduct thermal insulation performance tests. The results are as follows: Figure 4 As shown in A and B.

[0171] Depend on Figure 4 It can be seen that the performance of the silica aerogel composite material is far better than that of the aramid honeycomb panel. The silica aerogel composite material prepared by the present invention is Figure 4 A) and low temperature ( Figure 4 B) conditions have excellent thermal insulation properties.

[0172] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A silicon oxide aerogel composite material, characterized in that: The invention comprises a framework matrix having pores and a silicon oxide aerogel; The silica aerogel is embedded in at least part of the pores of the framework matrix; The frame matrix includes aramid honeycomb panels, wheat straw, and hollow fibers; The thickness of the aramid honeycomb panel is 1 mm to 6 mm; The diameter of the wheat straw is 3 mm to 6 mm; The inner diameter of the hollow fiber is 300 μm to 500 μm, and the outer diameter is 500 μm to 700 μm.

2. The silicon oxide aerogel composite material according to claim 1, characterized in that: In the silica aerogel composite material, the content of the silica aerogel is 34wt% to 70wt%, and the content of the framework matrix is ​​30wt% to 66wt%.

3. A method for preparing the silicon oxide aerogel composite material according to claim 1 or 2, characterized in that: include: Compounding the silicon oxide aerogel with the framework matrix to obtain a silicon oxide wet gel composite material; After aging the silicon oxide wet gel composite material, immersing it in a first solvent for primary replacement, and immersing it in a second solvent for secondary replacement to obtain a silicon oxide aerogel composite material precursor; The silicon oxide aerogel composite material precursor is dried to obtain a silicon oxide aerogel composite material.

4. The method for preparing the silicon oxide aerogel composite material according to claim 3, characterized in that: The drying is supercritical drying, and the temperature of the supercritical drying is 30° C. to 40° C., the time is 40 min to 60 min, and the pressure is 8 MPa to 12 MPa.

5. The method for preparing the silicon oxide aerogel composite material according to claim 3, characterized in that: The first solvent is at least one of water, ethanol and isopropanol, and the second solvent is at least one of ethanol and isopropanol.

6. The method for preparing the silicon oxide aerogel composite material according to claim 3, characterized in that: The aging treatment temperature is 60°C to 80°C and the time is 10h to 12h; And / or, the one replacement is multiple replacements, the number of the multiple replacements is 2 to 5 times, and the time of each replacement in the multiple replacements is 6 hours to 12 hours; And / or, the secondary replacement is several replacements, the number of the several replacements is 4 to 6 times, and the time for each replacement in the several replacements is 6 hours to 12 hours.

7. The method for preparing the silicon oxide aerogel composite material according to claim 3, characterized in that: The silicon oxide aerogel is prepared by the following steps: The organic siloxane, acetic acid aqueous solution, urea and surfactant are mixed and subjected to hydrolysis and condensation reaction to obtain silica sol; The silica sol is subjected to the action of a pH regulator to obtain a silica aerogel.

8. The method for preparing the silicon oxide aerogel composite material according to claim 7, characterized in that: The mass ratio of the organosiloxane, the acetic acid aqueous solution, the urea and the surfactant is (3-8): (12-18): (3-8): (0.5-1.5).

9. The method for preparing the silicon oxide aerogel composite material according to claim 7, characterized in that: The organosiloxane is at least one of methyltrimethoxysilane, ethyltrimethoxysilane, vinyltrimethoxysilane and propyltrimethoxysilane; And / or, the surfactant is at least one of cetyltrimethylammonium chloride, cetyltrimethylammonium bromide, and polyoxyethylene polyoxypropylene ether. And / or, the temperature of the hydrolysis condensation reaction is 60°C to 80°C and the time is 3h to 4h; And / or, the pH adjuster includes acetic acid solution, and the pH value after adjustment by the pH adjuster is 3-4.

10. A heat insulating material, characterized in that: The invention comprises the silicon oxide aerogel composite material as claimed in claim 1 or 2.

Citation Information

Patent Citations

  • Organic / inorganic phenolic resin hybrid aerogel and preparation method thereof

    CN105838022A